Perbedaan Tingkat Resiliensi Diri Mahasiswa Rantau dari Suku Batak di Universitas Sanata Dharma Ditinjau dari Jenis Kelamin - Lintang Safitri; Bernardinus Agus Arswimba (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Research objectives: 1) to determine whether there is a difference in self-resilience levels among Batak students based on gender, 2) to identify factors influencing the resilience of transient students, 3) to assess the level of self-resilience between male and female students, 4) to identify low-scoring resilience scale items that can be proposed as counseling topics. This study employed a quantitative approach with a comparative research design. Data collection utilized a survey method involving 60 respondents, comprising 30 male and 30 female Batak students at Sanata Dharma University. The validity test confirmed 60 valid items out of 72, and reliability was established with a Cronbach's Alpha of 0.756. Data analysis included an Independent Sample T-test to examine differences. The findings revealed: 1) no significant difference in resilience levels between male and female students 2) the resilience levels among male students were categorized as very high (17%), high (73%), and moderate (10%), 3) while female students were categorized as very high (17%) and high (83%), 4) several resilience scale items were identified as scoring low, suggesting areas that could benefit from counseling interventions.